PENENTUAN FAKTOR KONVERSI DALAM PROSES PENGOLAHAN ROTAN SEBAGAI DASAR PEMBAYARAN TARIF JURAN HASIL HUTAN DAN EFISIENSI PRODUKSI - Jasni Jasni; Osly Rachman; Jamaludin Malik (Jurnal Penelitian Hasil Hutan, 2001)
Conversion factor is a value representing the conversion in rattan processing. The convert mainly happened on physical properties such as moisture content and specific gravity. They convert volume and weight. That conversion factor is important to be determined accurately, because it will affect production cost and forest product's fee paid by rattan producer.Four species of a large and small diameter rattan were studied i.e. Seuti (Calamus omatus Bl), Bubuay (Plectocomia elongata Bl) Seel (Daemonorops melanochaetes Becc.) and Pelah (Daemonorops rubra Bl.). The conversion factor was counted on the basic of weight and volume decreas.The results indicated that conversion factor of large rattan from fresh rattan to polished are 35.641.2% by weight and 68.583.0% by volume. Conversion factor of small rattan that processed until splitting are 28.525.1%  skin and 7.39.8 % by core weight.